The Strategies to Increase Tourist Loyalty: The Role of Tourism Service Quality and Satisfaction in East Java Beach Tourism - Tri Palupi Robustin; Stephen Mago (Relasi : Jurnal Ekonomi, 2026)
East Java Province is one of the provinces in Indonesia with many tourist attractions, including beach tourism and fantastic scenery. Some beaches with fascinating scenery that many tourists in East Java visit are Papuma Beach in Jember, white sand beach in Situbondo and Red Island Beach in Banyuwangi. Researchers are interested in researching these beaches because they want to prove whether the quality of tourist services and tourist satisfaction on these beaches can create tourist loyalty. So, this research aims to determine the influence of tourism product quality and satisfaction on tourist loyalty in East Java's beach tourism industry. The type of research is associative research with a tourist population that has visited Papuma Beach, White Sand Beach and Pulau Merah Beach with a sample of 100 respondents. The sampling technique is purposive sampling with the criteria of tourist respondents who have visited the beach more than once. The data analysis technique uses multiple linear regression analysis. The results of the study concluded that the quality of tourism services and satisfaction have a partial effect on tourist loyalty. Furthermore, this research can contribute to developing management science studies, especially marketing management in the university environment, so that it can be a reference for similar research and further research.